15 лет деятельности Камчатской группы реагирования на вулканические извержения - Гирина О.А. (ИВиС ДВО РАН, 2008)
Kamchatkan Volcanic Eruption Response Team (KVERT), created in 1993 through a cooperative effort of Russian and U.S.A. scientists, analyses the data of monitoring of Kamchatkan and Northern Kurile volcanoes to provide warnings and rapid reporting eruptions. Scientists of KVERT work closely with Alaska Volcano Observatory, Airport Meteorological Center at Yelizovo Airport, the Tokyo Volcanic Ash Advisory Center (VAAC), Anchorage VAAC, Washington VAAC and the others to release timely eruption warnings.